Sturge-Weber syndrome-associated glaucoma and intraocular osseous metaplasia: a unique complicated case - Pavlenko, Dmytro (BMJ Case Rep, 2018)
A 30-year-old European man was admitted to our centre complaining about severe pain of the right eye (OD) and right part of the face, redness and no vision of the OD. He had an 18-year history of secondary to Sturge-Weber syndrome glaucoma, 6-month history of red eye and 1-week history of pain in OD. The best-corrected visual acuity was no light perception OD and 20/20 OS. Intraocular pressure was 36 mm Hg OD. Examination revealed endophthalmitis, Sturge-Weber syndrome-associated glaucoma and complicated cataract of OD. Unfortunately, no prescribed treatment helped this patient, so evisceration of OD was performed. During the evisceration, a subretinal 20 mm in width and 22 mm in length osseous tissue, partially vascularised, was removed surgically and was sent to the histological laboratory. Histopathologically, there were data of active inflammatory process, retinal detachment due to huge subretinal osseous metaplasia, gliosis and retinal pigment epithelial hyperplasia, and druses with ossification.